Towards sustainable pedestrian mobility in Riyadh city, Saudi Arabia: A case study. (June 2021) - Sultan, B.; Katar, I.M.; Al-Atroush, M.E.
Highlights: Factors affecting the traveling patterns and behavior of individuals in Riyadh city are discussed. A reliable assessment method for pedestrian mobility environment is presented. Individual's willingness to switch to more sustainable mobility choices is investigated. Abstract: A new public transportation network is currently being constructed in Riyadh city. Public buses and Riyadh metro are expected to be available for the passengers shortly. Based on the Saudi Vision 2030, the government directed billions of dollars to rehabilitate the infrastructures and sidewalks to support the national transformation to sustainable mobility. With that in mind, understanding the individual's choice of mobility mode is necessary to adopt appropriate planning and management policies. In this paper, a comprehensive assessment study has been carried out to examine the individual's travel patterns in Riyadh city through a case study of the Prince Sultan University's (PSU) community and evaluate the pedestrian environment's quality around the campus. Individuals' travel patterns were analyzed using a web-based survey addressed to the PSU community, including; Students, Faculty, and Staff. Moreover, the quality of the pedestrian's environment was in-situ evaluated based on well-defined indicators. The results of this assessment addressed the factors influencing the pedestrian mode choice and highlighted the barriers that may delay the transformation to sustainable mobility. Based on this study's conclusions, several recommendations have been proposed to promote the transformation to sustainable mobility in Riyadh city.